PENGARUH PAPARAN SINAR MATAHARI PAGI TERHADAP PENURUNAN TANDA IKTERUS PADA IKTERUS NEONATORUM FISIOLOGIS - Puspitosari, Ratih Dewi; Sumarno, Sumarno; Susatia, Budi (Jurnal Kedokteran Brawijaya, 2006)
Physiological jaundice is a sign usually happens tonewborn infants. The cause of icterus is the increase of indirect bilirubin that makes the skin yellow that usually disturb the people. Treatment of this yellow baby is  by exposing them to the morning sun. Sun exposure can reduce jaundice skin by changing the bilirubin indirect molecule. This research aim was to know the effect of morning sun exposure thatcan decrease jaundice skin through jaundice skin level measurement on babies. The special goal of the research was to know the jaundice skin and the difference before and after expos to the sun. The research was a quasi experimental study. The samples consisted of 5 babies,  selected by quota sampling. The measured variables were morning sun exposure and jaundice skin level. The research was done by exposing the samples on the morning sun for 30 minutes, then the jaundice skin measured in minutes 0,  5th, 10th, 15th, 20th, 25th, and 30thby using Corel Photo-Paint 12 Program. Data analysis was done with ANOVA and was continued by correlation-regression test, with confidence interval 99%.